Development of a 32-bit floating point 3 dimensional vector microprocessor - Dacuycuy, Michael B. (1997)
The aim of the project is to develop a three dimensional vector microprocessor modelled in VHDL (Very High Speed Integrated Circuit Hardware Description Language). It is patterned after scalar processor-based design architectures implemented in multiple cycles but it is not pipelined. It can perform vector operations like adding vectors, subtracting vectors, multiplying a vector with a scalar, and getting the dot and the cross products. All operands are in floating point format patterned after the IEEE 754 Single Precision Floating Point Format.